Design and Simulation of low cost Root Crop Harvester - Sharma Ratnesh; Kumar Shiv Ranjan; Chouhan Surpal Singh; Yadav Udit (Open Agriculture, 2019)
In India agriculture is one of the most important sources of employment for the farmers and almost everything depends on agriculture. Root vegetables and crops are hard to remove from the soil and it takes much of the farmer’s time. Even after removing these crops manually farmers are not able to achieve 100% recovery of the crops. When these crops are taken out manually this process require many precautions from the farmer. Due to human error approximate 20-30% of root vegetables and crops are left out in the field. Rich farmers can afford the proper machinery to cultivate the root crops but poor farmers are not able to afford such types of machinery. Hence, the objective of the present study was to design and simulate low cost root crop harvesting machines for poorer farmers. The machine consists of a frame, chain drive, gears, shaft, seed drill ground wheel, plough and storage container. All the measurements, dimensions and material selections were taken as per ASTM-A36 and the design hand data book. The design of the Root Crop Harvester was done mathematically and finally validated using CAD software.